MODEL PEMBELAJARAN DISKOVERI SEBAGAI STRATEGI PEMBELAJARAN BAHASA ARAB - Erta Mahyudin (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2014)
Teaching strategy is very important in Arabic Classroom. It covers design and dimension. One of the model in the instructional design is discovery learning. In teaching Arabic language discovery model called guided discovery. In this model the exposure of linguistic material is given firstly, and followed by the rule of language. DOI: 10.15408/a.v1i2.1139